Impact of crisis on regional development in Croatia - Irena Dokic; Ivana Rasic Bakaric; Zlatan Fröhlich (European Regional Science Association (ERSA), 2014)
The economic crisis has affected the EU regions very differently over the last five years, depending on the region's strengths or weaknesses, its sectoral structure and the response of national and regional governments. In some countries, downturns can lead to narrower interregional disparities, while in some can trigger regional divergence. Previous empirical studies indicate that there is a tendency for regional disparities to grow during recessions, and diminish in the period of economic growth (Dunford and Parron, 1994; Evans and MacCormic, 1994, Audas and Mackay, 1997). Although the reduction of regional disparities represents one of the priorities of EU regional policy and of Croatian regional policy, regional disparities within the Croatia are still significant. The current economic crisis that has emerged in the Croatian economy has already an enormous negative effect on several national and regional development indicators like GDP per capita, unemployment, and productivity. Some areas are coping with structural changes such as de-industrialization. In line with that the main aim of the paper is to find out if regional imbalances within Croatia have been more exposed by the current crises? This paper analyses the disparities between economic developments of Croatian counties before the crisis (before 2009) in comparison with the recession period. The analysis focuses on regional development index and other available socio-economic indicators (GDP per capita, unemployment rate). Obtained results can serve as a ground for improvements in Croatian regional economic policy.
Keywords: O18; R11; R58; 330; economic crisis; regional disparities; convergence and divergence